2011
DOI: 10.1007/s10533-011-9644-5
|View full text |Cite
|
Sign up to set email alerts
|

Methanogen diversity and community composition in peatlands of the central to northern Appalachian Mountain region, North America

Abstract: Methanogenic archaea are ubiquitous in peat soils; however, their diversity and distributions within and among peatland ecosystems are not well known. We used comprehensive clone libraries of 16S rRNA gene sequences to investigate spatial patterns in diversity (richness, evenness of taxa) and composition (taxonomic, phylogenetic) of the methanogenic community in six peatlands arrayed 775 km from eastern Ontario, Canada to West Virginia, USA. Five sites were Sphagnum (moss) and shrub dominated; one site was sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
50
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 84 publications
9
50
0
1
Order By: Relevance
“…The two sites on about the same latitude, SM and LV (Table 1) showed similar abundance, activity and diversity of methanogens, while all these characteristics were lower at the high latitude DS site. This is in accordance with the discussion forwarded by Yavitt et al (2011) for the diversity variation found among North American peatbogs, i.e. the diversity variation may be related to geographical distances.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The two sites on about the same latitude, SM and LV (Table 1) showed similar abundance, activity and diversity of methanogens, while all these characteristics were lower at the high latitude DS site. This is in accordance with the discussion forwarded by Yavitt et al (2011) for the diversity variation found among North American peatbogs, i.e. the diversity variation may be related to geographical distances.…”
Section: Discussionsupporting
confidence: 92%
“…the diversity variation may be related to geographical distances. The distance between the two southern bogs was within the range for those observed with similar diversities by Yavitt et al (2011), while the northern site is separated by about 1000 km from the LI and SM sites in the present study (Table 1). In a parallel study (Robroek et al, 2014), investigating the plant composition and ecological functions, observed that the plant species richness and plant diversity variation were similar for the southern sites (LV and SM) but differed from the northern site (DS).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Therefore in earlier there was a proof for niche adaptation in methanogens (Yavitt et al, 2012) and methanotrophs (Kumaresan et al, 2011;Nazaries et al, 2011). But after that, Reim and colleagues (2012) detected vertical niche differentiation in gamma proteobacterial methanotrophs inside the first three milli metres of water saturated soils.…”
Section: Current Status and Future Perspectivementioning
confidence: 99%